VHL-P138R and VHL-L163R Novel Variants: Mechanisms of VHL Pathogenicity Involving HIF-Dependent and HIF-Independent Actions - Mathó, Cecilia; Fernández, María Celia; Bonanata, Jenner; Liu, Xian-De; Martin, Ayelen; Vieites, Ana; Sansó, Gabriela; Barontini, Marta; Jonasch, Eric; Coitiño, E. Laura; Pennisi, Patricia Alejandra (Frontiers in Endocrinology, 2022)
von Hippel-Lindau disease is an autosomal dominant cancer syndrome caused by mutations in the VHL tumor suppressor gene. VHL protein (pVHL) forms a complex (VBC) with Elongins B-C, Cullin2 and Rbx1. Although other functions have been discovered, the most described function of pVHL is to recognize and target hypoxia inducible factor (HIF) for degradation. This work comprises the functional characterization of two novel variants of the VHL gene (P138R and L163R) that have been described in our center in patients with VHL disease by in vitro, in vivo and in silico approaches. In vitro, we found that these variants have a significantly shorter half-life compared to wild type VHL, but still form a functional VBC complex. Altered fibronectin deposition was evidenced for both variants using immunofluorescence. In vivo studies revealed that both variants failed to suppress tumor growth. By means of molecular dynamics simulations, we inspected in silico the nature of the changes introduced by each variant in the VBC complex. We have demonstrated the pathogenicity of P138R and L163R novel variants, involving HIF dependent and HIF independent mechanisms. These results provide the basis for future studies regarding the impact of structural alterations on post translational modifications that drive pVHL’s fate and functions.